2001
DOI: 10.1111/j.1741-3729.2001.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

RELATE: Relationship Evaluation of the Individual, Family, Cultural, and Couple Contexts*

Abstract: The purpose of this article is to present the conceptual model underlying RELATE, a relationship evaluation instrument, and to describe how this instrument can be used by instructors, clinicians, and therapists. The RELATE model contains measures of the 4 primary contexts of a couple's experience: the individual, the family, the culture, and the couple. The model includes some of the primary variables in Gottman's marital cascade and has been evaluated for reliability and validity. Examples of how to use the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
305
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 251 publications
(311 citation statements)
references
References 21 publications
(28 reference statements)
4
305
0
2
Order By: Relevance
“…Couples generally reported high satisfaction levels (M = 3.99, SD = 0.71). The RELATE satisfaction measures employed in this study have shown high test-retest reliability (between 0.76 and 0.78) and validity data have consistently shown that this scale is highly correlated with an existing relationship satisfaction and quality scale (Revised Dyadic Adjustment Scale) in both cross-sectional and longitudinal research (Busby et al, 2001(Busby et al, , 2009.…”
Section: Couple Outcomesmentioning
confidence: 91%
See 3 more Smart Citations
“…Couples generally reported high satisfaction levels (M = 3.99, SD = 0.71). The RELATE satisfaction measures employed in this study have shown high test-retest reliability (between 0.76 and 0.78) and validity data have consistently shown that this scale is highly correlated with an existing relationship satisfaction and quality scale (Revised Dyadic Adjustment Scale) in both cross-sectional and longitudinal research (Busby et al, 2001(Busby et al, , 2009.…”
Section: Couple Outcomesmentioning
confidence: 91%
“…''Responses were measured on a 5-point scale (1 = never to 5 = very often). In terms of test-retest and validity information on this scale, the communication items have been shown to have test-retest values between 0.70 and 0.83 and were appropriately correlated with a version of a commonly used Relationship Quality measure as predicted (Busby et al, 2001). Also, this scale has been shown in longitudinal research to be predictive of couple outcomes and are amenable to change in couple interventionstudies thatfocusoncommunication (Busby et al, 2007).…”
Section: Couple Outcomesmentioning
confidence: 93%
See 2 more Smart Citations
“…Existem algumas medidas de funcionamento marital que também incluem subescalas de empatia (e.g., Barrett-Lennard Relationship Inventory; Barrett-Lennard, 1962;Wampler & Powell, 1982;Relationship Evaluation Questionnaire;Busby, Holman, & Taniguchi, 2001), contudo elas têm recebido pouca atenção empírica e não se demonstraram capazes para distinguir componentes emocionais e cognitivos da empatia. Considerando evidência que sugere que a empatia cognitiva e emocional pode desempenhar papel distinto no ajustamento relacional (Davis & Oathout, 1987), era central a existência de uma medida multidimensional de empatia diádica.…”
Section: Discussionunclassified